Which Cytological Characteristics are More Valuable for Papillary Carcinoma in Thyroid Fine-needle Aspiration? - Cansu Benli Işık; Halide Nur Ürer; Kamile Altundal; Mehmet Zeki Günlüoğlu; Pınar Fırat (Haseki Tıp Bülteni, 2017)
Aim: Fine-needle aspiration plays a significant role in the evaluation of solitary thyroid nodules. Several cytological criteria are defined and these primarily aim to distinguish papillary carcinoma (PC), the most common thyroid malignancy, from other benign diseases. In our study, we aimed to determine which cytologic criteria are more valuable in diagnosing PC. Methods: Patients, who had undergone thyroidectomy operation between January 2013 and December 2014 and had preoperative fine-needle aspiration cytology, were screened. Among cases that were postoperatively diagnosed as benign, 62 cases and among those diagnosed as PC and papillary microcarcinoma, 24 cases were included in this study. The cytologic criteria were reassessed. In the linear regression analysis, the variables associated with the diagnosis of malignancy at the level of p<0.05 were considered significant for predicting the diagnosis of PC. Results: The variables that remained as predictive for the diagnosis of cancer as the result of the Backward analysis following the multivariate analysis performed with the variables with a p value of less than 0.1 were cellular pleomorphism, nuclear atypia, papillary structures with fibrovascular cores, and intranuclear pseudoinclusion. Conclusion: Although every cytological feature is characteristic for PC, none of them alone is specific; they should be evaluated together with all nuclear and structural features during the diagnostic approach.